Thyroid Surgery and Inadvertent Removal of Parathyroids - YUMUŞAKHUYLU, ALİ CEMAL; OYSU, ÇAĞATAY; İNCAZ, SEFA (SPRINGER INDIA, 2021)
This study aimed to determine the incidence of inadvertent parathyroid removal during thyroid surgery and define its associated risk factors. In this single-center record-based study, we retrospectively analyzed the clinical and pathological records of 462 patients undergoing thyroidectomy. Incidental parathyroidectomy was detected in 61 of 462 patients (13.2%). The incidence of inadvertent parathyroid removal was 17.6% (36 of 205 patients) in patients having malign thyroid diseases, compared with 9.7% (25 of 257 patients) in patients with benign thyroid diseases (p = 0.045). Incidentally removed parathyroid tissue was intrathyroidal in 8 of the 61 patients. Thus, the ratio of intrathyroidal parathyroid tissue among all patients was 1.7% (8 out of 462). Central neck dissection was carried out in 40 patients (8.7%). Fourteen of these 40 patients (35%) had an incidental parathyroid in their specimen compared with 47 of 422 patients (11.1%) who did not undergo central neck dissection (p<0.001). Incidental parathyroidectomy occurred in 13.2% of patients undergoing thyroidectomy in our study. The majority of patients had one parathyroid identified in their specimen. Central neck dissection was significantly predictive for incidental parathyroidectomy. Well-trained senior otolaryngology residents can safely perform thyroid surgery with similar rates of incidental parathyroidectomy as their masters.
Keywords: Thyroidectomy; Parathyroid; Thyroidectomy complication; Unintentional parathyroidectomy; ANATOMY